Algorithm 758: VLUGR2 a vectorizable adaptive-grid solver for PDEs in 2D. - Blom, J. G. (ACM transactions on mathematical software.)
This article deals with an adaptive-grid finite-difference solver for time-dependent two-dimensional systems of partial differential equations. It describes the ANSI Fortran 77 code, VLUGR2, autovectorizable on the Cray Y-MP, that is based on this method. The robustness and the efficiency of the solver, both for vector and scalar processors, are illustrated by the application of the code to two example problems arising from a groundwater-flow model.